The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.14715/cmb/2021.67.6.7
|View full text |Cite
|
Sign up to set email alerts
|

Curcumin reduces inflammation in mice with the psoriasis model by inhibiting NLRP3 inflammatory bodies

Abstract: As a chronic skin disease, psoriasis is a relatively common disease among various types of skin diseases. Because this disease is often distributed throughout the patient's body and is prone to develop, it is difficult to guarantee the quality of life and physical and mental health of patients with this disease. The purpose of this article is to investigate whether curcumin can effectively inhibit the NLRP3 inflammatory body and thereby reduce the inflammation in the mouse psoriasis model. Through the use of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 15 publications
(15 reference statements)
0
10
0
Order By: Relevance
“…There have already been reports of the biological effects of turmeric [16][17][18][19][20][21][22] .…”
Section: Results and Disscusionmentioning
confidence: 99%
“…There have already been reports of the biological effects of turmeric [16][17][18][19][20][21][22] .…”
Section: Results and Disscusionmentioning
confidence: 99%
“…Curcumin inhibited NADPH oxidase and reduced endogenous ROS, thereby inhibiting lipopolysaccharide-induced inflammation [ 144 ]. Moreover, curcumin alleviated skin damage in psoriatic mice by decreasing IL-22 and IL-18 expression with a 47% inhibition rate [ 151 ]. This study also reported that curcumin protected the skin by neutralizing free radicals and inhibiting MAPK and NF-κB signaling pathways.…”
Section: Therapeutic Potential Of Plant Polyphenolsmentioning
confidence: 99%
“…This study also reported that curcumin protected the skin by neutralizing free radicals and inhibiting MAPK and NF-κB signaling pathways. Thus, AP-1 transcription and production of cytokines (e.g., IL-33, TNF-α, IL-4, IL-5, IL-13, and IL-31) were inhibited by curcumin, thereby reducing skin inflammation in psoriatic and AD mice [ 150 , 151 , 152 , 228 ].…”
Section: Therapeutic Potential Of Plant Polyphenolsmentioning
confidence: 99%
“…Zhang et al [33] induced breast cancer in mice and reported that curcumin administration reduced NF-KB levels as well reduced activation of the ubiquitin proteasome system leading to less cachexia in these mice. However, the reduced circulating cytokine levels scene with curcumin administration could also have increased the muscle protein synthesis side of the muscle protein balance equation.…”
Section: Curcuminmentioning
confidence: 99%